Peningkatan Kualitas Hidup Orang Dengan Gangguan Jiwa Dengan Self Help Group Di Kota Surakarta - Endang Caturini; Insiyah Insiyah (Poltekkes Kemenkes Surakarta, 2020)
Introduction: People who experience mental disorders who experience various problems, with different symptoms, generally they have characteristics with some combination of abnormal thoughts, emotions, behavior and relationships with other people that manifest in the form of a series of symptoms and / or changes in behavior which is meaningful and can cause suffering and obstacles in carrying out people's functions as humans (UU Kesehatan no 18 tahun 2014; WHO, 2017; & WHO, 2018). This is a serious health problem, which usually has problems with poor quality of life. They are associated with feelings of distress, lack of control over symptoms and life in general, negative perceptions of self, stigmatization and rejection, reduced activity and difficulty with daily functioning, and negative outlook. (Connell, J, Brazier, J, O'Cathain, A, Jones, M.L. & Paisley, S., 2012). Group interventions carried out by nurses such as group activity therapy, supportive therapy and self-help groups to help individuals improvement in their quality of life. Group therapy, one of the self help group, is a group where each member has the same desire to overcome mental disorders or increase the level of cognitive or emotional well-being among group members (Sulistyowati., E.C. & Sulistyowati D, 2018). Self Help Group aims to develop empathy among fellow group members where fellow group members provide mutual reinforcement which has an impact on improving the quality of life. This study aims to determine the improvement of the quality of life of people with mental disorders (ODGJ) with the self help group in the city of Surakarta. Methods: This was a quasi-experimental study with a pre-post test control group design. Data were taken before and after giving the intervention of self-help groups of schizophrenia patients in the intervention group. The total sample was 160 clients divided into 2 groups, namely 80 respondents for group 1 at Griya PMI and 80 respondents for group 2 at RSJD Dr Arif Z Surakarta, each group consisting of 40 respondents for intervention and 40 respondents for the control group. This study measures the quality of life with a research instrument using a life quality questionnaire. Data were analyzed using Paired t-test, Wilcoxon signed ranks test, independent t-test and Mann Whitney-test. Results: The study proved that there was a statistically significant difference in the quality of life before and after giving the self help group (p value, 0.000) between the intervention group and the control group, both at Griya PMI with a mean difference of 20.23 and at RSJD Dr. Arif Z. self help group with a mean difference of 10.85. Conclusion: self help group which is used for intervention is considered effective to improve quality of life. Suggestion: self help group is used as a mental nursing group intervention in caring for mentally ill patients.